2017
DOI: 10.1021/acs.jmedchem.6b01766
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytostatic and Antiviral Profiling of Thieno-Fused 7-Deazapurine Ribonucleosides

Abstract: Two isomeric series of new thieno-fused 7-deazapurine ribonucleosides (derived from 4-substituted thieno[2',3':4,5]pyrrolo[2,3-d]pyrimidines and thieno[3',2':4,5]pyrrolo[2,3-d]pyrimidines) were synthesized by a sequence involving Negishi coupling of 4,6-dichloropyrimidine with iodothiophenes, nucleophilic azidation, and cyclization of tetrazolopyrimidines, followed by glycosylation and cross-couplings or nucleophilic substitutions at position 4. Most nucleosides (from both isomeric series) exerted low micromol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 44 publications
(65 reference statements)
3
80
1
Order By: Relevance
“…All the title compounds were submitted for screening of biological activities. They were tested for cytotoxic activity on a panel of leukemia (CCRF‐CEM, CEM‐DNR, K562, and K562‐TAX) and cancer cell lines (A549, HCT116 and HCT116p53‐/), for antiviral activity (hepatitis C virus, dengue, HIV, respiratory syncytial virus, influenza, coxsackie and herpes viruses) and for antibacterial activity ( Staphylococcus aureus 4591, Enterococcus faecium 419/ANA, Enterococcus faecalis CCM 4224, Escherichia coli CE5556, Pseudomonas aeruginosa R, Candida albicans CCM 8161 and Staphylococcus aureus CCM 3953 ) . However, all the final compounds were found inactive (IC 50 > 50 µ m ) in these assays, suggesting that the ribose moiety is crucial for cytotoxic activity of this class of nucleosides and that installing of a stable phosphate surrogate does not increase the activity.…”
Section: Chemistrymentioning
confidence: 99%
“…All the title compounds were submitted for screening of biological activities. They were tested for cytotoxic activity on a panel of leukemia (CCRF‐CEM, CEM‐DNR, K562, and K562‐TAX) and cancer cell lines (A549, HCT116 and HCT116p53‐/), for antiviral activity (hepatitis C virus, dengue, HIV, respiratory syncytial virus, influenza, coxsackie and herpes viruses) and for antibacterial activity ( Staphylococcus aureus 4591, Enterococcus faecium 419/ANA, Enterococcus faecalis CCM 4224, Escherichia coli CE5556, Pseudomonas aeruginosa R, Candida albicans CCM 8161 and Staphylococcus aureus CCM 3953 ) . However, all the final compounds were found inactive (IC 50 > 50 µ m ) in these assays, suggesting that the ribose moiety is crucial for cytotoxic activity of this class of nucleosides and that installing of a stable phosphate surrogate does not increase the activity.…”
Section: Chemistrymentioning
confidence: 99%
“…Janus‐type nucleosides 41a ‐ b showed moderate anti‐HCV activities (EC 50 = 5.7 and 3 μM, respectively) which was accompanied by cytotoxicity toward Vero, CEM, and PBM cell lines . Anti‐HCV screening of thieno‐fused 7‐deazapurine ribonucleosides showed that derivatives 44c , e and 45c‐e possess submicromolar activities and do not show any cytotoxic effect against the replicon cells . The anti‐HCV potency of these compounds is similar to that of anti‐HCV agent mericitabine.…”
Section: Nucleosides With Antiviral Activitiesmentioning
confidence: 87%
“…Initial studies of mode of action of compounds 44c ‐ e and 45c ‐ e revealed RNA synthesis inhibition and decrease in mitotic cell fraction in cell cycle analysis. Both compounds 44e and 45e are efficiently phosphorylated both in normal and cancer cells indicating that cell‐type specific phosphorylation is not a reason for the different selectivities of series 44 and 45 . In conclusion, even though the family of fused nucleosides is relatively small, it has already brought interesting compound hits and deserves further development as a source of cytotoxic nucleosides.…”
Section: Cytotoxic Nucleosidesmentioning
confidence: 96%
See 1 more Smart Citation
“…Next, we sythesized various 4‐substituted 5(6)‐(het)arylpyrimido[4, 5‐ b ]indole nucleosides 2 , and also found some antiviral activities (dengue and HCV 1 A and 1B replicons) with no significant cytotoxicity. The lack of cytotoxic or cytostatic activity of pyrimidoindole nucleosides 1 and 2 motivated us to reduce the size of the fused ring and to prepare two series of thieno‐fused 7‐deazapurine nucleosides 3 and 4 . These nucleosides also displayed submicromolar anti‐HCV activities, but the methyl, methoxy and methylsulfanyl derivatives were strong nanomolar cytostatics with no/low toxicity to nonmalignant cells showing promising therapeutic index.…”
Section: Introductionmentioning
confidence: 99%